Biometry of the fishes Barbus plebejus and Barbus capito from Coruh Basin, Turkey - Kemal Solak; Ali Alas; Muhittin Yilmaz; Ahmet Öktener (Revista de Biología Tropical, 2009)
Metric and meristic characters are important to identify fish species and their habitat peculiarities. There are many species that belong to the fish genus Barbus, which is found in tropical and extratropical regions, but there are few studies covering the Coruh basin. Two subspecies of Barbus were found in the Coruh River system of Eastern Anatolia, Turkey: Barbus plebejus escherichi and Barbus capito capito. We collected specimens in seven localities for measurement. The number of vertebra were determined radiographically. Some specimens of B. capito capito have a sharper snout in the segments of Coruh where the water flows faster, suggesting a modification related to current. The biometric measurements vary geographically and could be related to abiotic and biotic factors in the habitat. Rev. Biol. Trop. 57 (1-2): 159-165. Epub 2009 June 30.